2013
DOI: 10.1002/mds.25561
|View full text |Cite
|
Sign up to set email alerts
|

AFQ056 in Parkinson patients with levodopa‐induced dyskinesia: 13‐week, randomized, dose‐finding study

Abstract: AFQ056 is a novel, selective metabotropic glutamate receptor 5 antagonist. This was a 13-week, double-blind, placebo-controlled study. Patients with Parkinson's disease and moderate-to-severe levodopa (l-dopa)-induced dyskinesia who were receiving stable l-dopa/anti-parkinsonian treatment and were not currently receiving amantadine were randomized to receive either AFQ056 (at doses of 20, 50, 100, 150, or 200 mg daily) or placebo (1:1:1:1:2:3 ratio) for 12 weeks. The primary outcome was the modified Abnormal I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
1
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 23 publications
(23 reference statements)
6
78
1
4
Order By: Relevance
“…A third strategy that has led to specific targets for therapeutic trials has come from studies of drugs that suppress levodopa-induced dyskinesias in Parkinson's disease or its animal models. Dyskinesias sometimes have a dystonic quality, and negative allosteric modulators of metabotropic glutamate receptor mGluR5 appear to specifically suppress dystonic dyskinesias in animal models [25,26]. These observations raise the intriguing possibility that this category of drugs may suppress dystonia in other disorders, but further studies are needed.…”
Section: Potential Sources Of Novel Dystonia Drugsmentioning
confidence: 99%
“…A third strategy that has led to specific targets for therapeutic trials has come from studies of drugs that suppress levodopa-induced dyskinesias in Parkinson's disease or its animal models. Dyskinesias sometimes have a dystonic quality, and negative allosteric modulators of metabotropic glutamate receptor mGluR5 appear to specifically suppress dystonic dyskinesias in animal models [25,26]. These observations raise the intriguing possibility that this category of drugs may suppress dystonia in other disorders, but further studies are needed.…”
Section: Potential Sources Of Novel Dystonia Drugsmentioning
confidence: 99%
“…The development of mavoglurant or AFQ056 [methyl (3aR,4S,7aR)-4-hydroxy-4-[(3-methylphenyl) ethynyl]octahydro-1H-indole-1-carboxylate] (Vranesic et al, 2014) for the treatment of dyskinesia induced by L-DOPA (L-3,4-dihydroxyphenylalanin) (Stocchi et al, 2013) has been discontinued in view of its reported insufficient efficacy (Petrov et al, 2014). More recently, the clinical development of mavoglurant and basimglurant for fragile X syndrome (FXS) also has been discontinued because neither drug improved the clinical phenotype of patients (FRAXA mavoglurant posting, FRAXA basimglurant posting), an unexpected result in view a strong hypothesis (Krueger and Bear, 2011;Michalon et al, 2012;Scharf et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PD therapy strategies that moderate G protein signaling and neuronal excitability while maintaining normal movement may be an ideal way to eliminate DA receptor-associated dyskinesias. To moderate this uncontrolled signaling or neuronal excitability, several approaches have been explored such as reducing D1R surface expression (29,30), dampening overactive intracellular signaling (20,23,31,32), and inhibiting A2A (33,34), mGluR5 (35)(36)(37) or NMDA receptors (24,25,(38)(39)(40). Although these targets have clinical potential, several drugs to these targets have either failed clinical trials or have the potential to affect other key CNS physiological processes.…”
mentioning
confidence: 99%